2023
DOI: 10.1111/dar.13601
|View full text |Cite
|
Sign up to set email alerts
|

Encounters with police drug detection dogs at music festivals amongst people who regularly use ecstasy and/or other illicit stimulants in Australia

Abstract: Introduction Despite increasing evidence challenging the effectiveness and legality of police drug dog operations, these strategies remain common. We aimed to describe drug dog encounters at music festivals, behavioural adaptations taken in anticipation of their presence and consequences of encounters amongst a sample of people who regularly use MDMA/ecstasy. Methods Data were collected via interviewer‐administered questionnaires in April–June 2019. Australians aged 16 years or older who used MDMA/ecstasy and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Table 3 presents the geography, methodology, and synthesis of the themes identified across the sample. Not all national studies collected data in every Australian jurisdiction, however the majority ( n = 11) had done so (Black et al, 2008; Dietze et al, 2015; Dunn et al, 2006; Gibbs et al, 2023; Johnston et al, 2006; Peacock et al, 2019, 2021; Sindicich & Burns, 2011, 2015; Sindicich et al, 2016; Uporova et al, 2018). Of the 15 national studies, 11 reported on data from the EDRS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 3 presents the geography, methodology, and synthesis of the themes identified across the sample. Not all national studies collected data in every Australian jurisdiction, however the majority ( n = 11) had done so (Black et al, 2008; Dietze et al, 2015; Dunn et al, 2006; Gibbs et al, 2023; Johnston et al, 2006; Peacock et al, 2019, 2021; Sindicich & Burns, 2011, 2015; Sindicich et al, 2016; Uporova et al, 2018). Of the 15 national studies, 11 reported on data from the EDRS.…”
Section: Resultsmentioning
confidence: 99%
“…Just over half of the studies ( n = 13) solely collected quantitative data through surveys (Allott & Redman, 2006; Barratt et al, 2018) and interviews, which was significantly influenced by the 11 EDRS outputs utilizing a structured interview methodology (Black et al, 2008; Dietze et al, 2015; Dunn et al, 2006; Gibbs et al, 2023; Johnston et al, 2006; Peacock et al, 2019, 2021; Sindicich & Burns, 2011, 2015; Sindicich et al, 2016; Uporova et al, 2018). Four studies collected both qualitative and quantitative data via surveys (Day et al, 2018; Southey et al, 2020) and interviews (Copeland et al, 2006; Gascoigne et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations